Penambahan Ekstrak Daun Pegagan (Centella Asiatica) Terhadap Mutu Kimia Susu Pasteurisasi Selama Penyimpanan Suhu Dingin - Kusumaningrum, Intan; Hapsari, Distya Riski; Hastuti, Arti; Amelia, Lia (JURNAL AGROINDUSTRI HALAL, 2025)
Pasteurized milk with the addition of gotu kola leaf extract has higher total phenols and antioxidant activity than pasteurized milk alone. Therefore, pasteurized milk with the addition of extracts has the potential to improve its storage quality. This experiment aimed to study the quality of pasteurized milk with the addition of gotu kola extract, which was stored at 5°C for nine days. This research consists of factor A, namely the addition of gotu kola leaf extract with four different treatment levels (A1 = 0%, A2 = 0.25%, A3 = 0.50%, A4 = 0.75%) and Factor B, namely storage time, between 0 and 9 days with an interval of 3 days (0, 3, 6, and 9 days). The research results showed that the greater the addition of gotu kola leaf extract and the longer the storage time, the lower the pH value and protein content, increase the total acid, and a positive alcohol test. Adding gotu kola leaf extract to milk reduces the storage period by up to three days, compared to the storage period of up to six days for pasteurized milk without extract.